Tradiciones para potencializar el turismo cultural en el cantón Durán provincia del Guayas - Rodriguez Robles, Juliana Lilibeth (2022)
The present investigation defines the importance of the traditions of the Canton Durán province of Guayas to strengthen the cultural tourism in the place, with the purpose of making the population aware of the sense of valorization and of its cultural richness through the traditions that have been transmitted and that nowadays are being lost. The traditions of the Canton of Durán are influenced by new technologies and, therefore, by the lack of interest of its authorities in promoting cultural tourism there. Its community is committed to contribute so that these cultural traditions are not forgotten and are perpetuated from generation to generation. This case study aims to analyze cultural tourism to contribute to traditional customs, allowing the flow and increase of tourists driven by the knowledge of the traditions of the canton, such as: gastronomic fairs, livestock fairs, boat rides on the Guayas, the great fair of Durán. It should be emphasized that with this case study the main beneficiaries are the citizens of the Canton Durán, because they would benefit in knowledge to contribute to the knowledge of the traditions that this canton has and thus strengthen cultural tourism and help the economy of each of the citizens and the place.